Speech Act Analysis of Greeting Form Found in Peacemaker Movie Series - I Ketut Adi Lanang Iswara; Komang Dian Puspita Candra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
The chosen movie series Peacemaker are the subject of the investigation, this study entitled “Speech Act Analysis of Greeting Form found in Peacemaker Movie Series” the study focused on greeting utterance produced by each characters in the Peacemaker movie series and concerns with the illocutionary acts that occur in the character’s utterance. It is aimed (1) to find out the types of illocutionary acts in the Peacemaker movie series, and (2) to analyze the function and meaning of the illocutionary act produced by the characters in the movie series. This study used descriptive qualitative method inanalyze the types and the function and meaning of illocutionary acts proposed by theory from Searle’s (1979). The result of this study showed that most of the data are expressive illocutionary act, second is followed with directive illocutionary act and the last is declarative illocutionary act that found in the Peacemaker movie series, in greeting utterance is hard to found greeting utterance that consist with assertive illocutionary act and commissive illocutionary act. The study conclude that the speaker has reason when they need someone to do the action through their greeting utterance. People are not only producing the greeting utterance to communicate but from the greeting utterance also has purpose they want to deliver to the hearer in purpose to understand the meaning of the greetings itself in directform or indirect form. Keyword: greeting utterance, illocutionary act, movie series peacemaker